2022
DOI: 10.3390/diagnostics12020506
|View full text |Cite
|
Sign up to set email alerts
|

2-[18F]FDG PET in the Management of Radioiodine Refractory Differentiated Thyroid Cancer in the Era of Thyrosin-Kinases Inhibitors: A Real-Life Retrospective Study

Abstract: Purpose To evaluate the role of 2-[18F]FDGPET/CT in the follow-up of radioiodine refractory thyroid cancer (RR-TC). Methods Forty-six 2-[18F]FDGPET/CT scans from 14 RR-TC patients were considered. Thyroid function tests: thyroglobulin (Tg), levothyroxine (LT4), and tyrosine-kinases inhibitors (TKIs) assumptions were recorded. Metabolic tumour volume (MTV) and total lesion glycolysis (TLG) were calculated from each scan and correlated with clinical parameters and the overall survival (OS). Results Baseline TLG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…89 Therefore, a multiparametric approach involving both morphological and metabolic data might be advisable in evaluating the tumour response during MKIs. 23 Real-life data confirmed the clinical benefit observed in clinical trials, but also revealed a reduced efficacy in comparison to the phase 3 studies, which normally include a more selected population. 90 Outside the registrative trials, the initial dosage of MKI is commonly chosen on an individualized basis, sometimes preferring an initial lower dose in case of poor PS and/or presence of several comorbidities.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…89 Therefore, a multiparametric approach involving both morphological and metabolic data might be advisable in evaluating the tumour response during MKIs. 23 Real-life data confirmed the clinical benefit observed in clinical trials, but also revealed a reduced efficacy in comparison to the phase 3 studies, which normally include a more selected population. 90 Outside the registrative trials, the initial dosage of MKI is commonly chosen on an individualized basis, sometimes preferring an initial lower dose in case of poor PS and/or presence of several comorbidities.…”
mentioning
confidence: 62%
“…Moreover, Tg levels might not reflect the tumour load in aggressive poorly differentiated TCs (PDTCs) that lose the ability to synthesize and/or secrete Tg. 23 Therefore, the isolated increase of Tg should not lead to the start of a MKI in the absence of evident structural disease progression.…”
Section: Characterization and Management Of Rai-r Tc Patients: How To...mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the presence of the BRAF V600E mutation and thyroglobulin doubling time <1 year are poor prognostic factors that we did not include in our analysis. A recent study confirmed that thyroglobulin correlated with overall survival but that MTV was not significantly correlated with thyroglobulin levels [ 56 ]. The retrospective design of our study did not allow for the reliable collection of thyroglobulin levels and BRAFV600E mutation of the included patients because blood samples were often analyzed in external laboratories and surgery was frequently conducted in a care center other than the Henri Becquerel Cancer Centre.…”
Section: Discussionmentioning
confidence: 97%
“…FDG PET/CT is particularly important for recurrence evaluation in differentiated thyroid cancer (DTC) patients having thyroglobulin elevation with negative iodine scintigraphy (TENIS) [ 95 ]. FDG PET/CT is also widely used to assess disease extent in patients with radioiodine-refractory DTC (RR-DTC) [ 96 ]. Given limited systemic therapeutic options, multiple tracers, including radiolabeled FAPIs have been tried in progressive RR-DTC with the ultimate aim of potential theranostics [ 97 ].…”
Section: Fapi Pet/ct—oncological Indicationsmentioning
confidence: 99%